The Strength of Proof of Letter C in Civil Cases at the Ponorogo Court - Putri Febrianawati, Nita; Suryono, Arier; Subekti, Rahayu (CV. Inara, 2024)
This research discusses the evidentiary power of Letter C certificates which are used as evidence in civil disputes in accordance with statutory regulations and jurisprudence. This research uses an empirical juridical method by examining a legal rule and then linking it to the reality in the field. The results of this research are that Letter C can be used as evidence in civil cases in court because Letter C is one of the first pieces of evidence that a person registers land with the National Land Agency to be used as evidence of an Authentic Deed in the form of a certificate. The author concludes that the judge's consideration granted the land ownership dispute in accordance with applicable regulations. The author's suggestion is for the community to convention their land rights so that they are in accordance with applicable regulations. The purpose of converting is so that the land owned has a strong legal basis. If it is not converted or registered there will be a big chance of a dispute occurring.